"Perrotta Human Defense Mechanisms Questionnaire (PDM-Q-v2)": Development, regulation and validation of a psychometric instrument for the identification of the functioning of individual Ego defense mechanisms - Giulio Perrotta (Archives of Depression and Anxiety - Peertechz Publications, 2023)
Introduction: To date, theorizations on the workings of psychological ego defense mechanisms are affected by the psychodynamic influence and theoretical scaffolding of the last century. There is a need to update theories and models to make them more consistent and modern with recent innovations in psychotherapy.  Materials and methods: A model related to the functioning of defense mechanisms was generated and the Perrotta Human Defence Mechanisms Questionnaire (PDM-Q-v2) was created to be administered to a selected population to compare it with the Defense Mechanisms Rating Scales-Self-Report-30 (DMRSSR- 30) and finally validate it.  Results: Statistical analysis showed that the psychometric test has a well-defined and stable construct (r = 0.999; p ≤ 0.001), with the variables well represented (r = 0.818; p ≤ 0.001) and positively correlated with another construct already validated (r = 0.766; p ≤ 0.001).  Conclusion: The Perrotta Human Defense Mechanisms Questionnaire (PDM-Q-v2) is a valid, efficient, and effective psychometric tool to identify the functioning or dysfunction of psychological ego defense mechanisms.